First case report of diagnosis of extrapancreatic solid pseudopapillary tumor with SMA invasion in a 47-year-old man: a case report and literature review - Zhang, Aijing; Wang, Kaibin; Tian, Xiaohan; Chen, Shuhai; Xu, Jianwei; Liu, Han; Wang, Lei; Li, Feng (Frontiers in Surgery, 2024)
Background: Solid pseudopapillary tumor of the pancreas (SPT) is a rare low-grade malignant tumor predominantly observed in young women without significant clinical symptoms. While most SPTs occur in the pancreatic region, rare cases have occurred in the retroperitoneum, making the diagnosis of ectopic SPTs difficult.Case presentation: Herein, we report a rare case of an extrapancreatic solid SPT with superior mesenteric artery (SMA) involvement in a 47-year-old man together with a literature review to provide context with clinical information, CT and a literature review.Conclusions: This case may provide a practical approach for the diagnosis of ectopic SPT, especially for patients with vascular invasion.